The Effect of Fintech Loans on Income Inequality in Indonesia - Saputri, Dtania; Andrianus, Fery (Dinasti Publisher, 2024)
This study aims to analyze the impact of FinTech loans on income inequality in Indonesia. The data utilized comprises 34 provinces in Indonesia with quarterly frequencies from 2019 to 2022. The use of provincial-level panel data enables subgroup analysis and differentiation based on FinTech loan levels for comparison purposes. The Two Step System Generalized Method of Moments (SYS-GMM) method is employed to address research questions and test the proposed hypotheses. Estimation results reveal that FinTech loans have a positive and significant impact on income inequality in Indonesia. Subgroup province analysis also indicates similar outcomes, with a greater influence observed in provinces with higher levels of FinTech loans.